2016
DOI: 10.1371/journal.pone.0164091
|View full text |Cite
|
Sign up to set email alerts
|

Depression among Parents Two to Six Years Following the Loss of a Child by Suicide: A Novel Prediction Model

Abstract: BackgroundParents who lose a child by suicide have elevated risks of depression. No clinical prediction tools exist to identify which suicide-bereaved parents will be particularly vulnerable; we aimed to create a prediction model for long-term depression for this purpose.MethodDuring 2009 and 2010 we collected data using a nationwide study-specific questionnaire among parents in Sweden who had lost a child aged 15-30 by suicide in years 2004-2007. Current depression was assessed with the Patient Health Questio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 46 publications
0
6
0
1
Order By: Relevance
“…Based on the 2011 baseline data from the China Health and Retirement Longitudinal Study 17 whose data cover 17,705 individuals aged 45 or older, living in 10,287 households in 450 rural villages or urban communities with 6,739 observations with complete information, the effects were significantly stronger for losing all the children, similar to losing the only child, than those having a living child or not losing, compared the mental health, happiness and loneliness after adjusting for demographic and socioeconomic characteristics. Previous research also has shown that bereaved parents exhibit more symptoms of depression, anxiety, loneliness, grief, and posttraumatic stress disorder than did their non-bereaved counterparts 18,19 . Meanwhile, bereavement was associated with long-term mortality due to illness (e.g., cancer), presumably because of stress, a weakened immune system, or poor health behaviors (e.g., smoking, alcohol consumption).…”
Section: The Difference Between Sdp and Other Bereavementmentioning
confidence: 90%
“…Based on the 2011 baseline data from the China Health and Retirement Longitudinal Study 17 whose data cover 17,705 individuals aged 45 or older, living in 10,287 households in 450 rural villages or urban communities with 6,739 observations with complete information, the effects were significantly stronger for losing all the children, similar to losing the only child, than those having a living child or not losing, compared the mental health, happiness and loneliness after adjusting for demographic and socioeconomic characteristics. Previous research also has shown that bereaved parents exhibit more symptoms of depression, anxiety, loneliness, grief, and posttraumatic stress disorder than did their non-bereaved counterparts 18,19 . Meanwhile, bereavement was associated with long-term mortality due to illness (e.g., cancer), presumably because of stress, a weakened immune system, or poor health behaviors (e.g., smoking, alcohol consumption).…”
Section: The Difference Between Sdp and Other Bereavementmentioning
confidence: 90%
“…Previous research has shown that bereaved parents exhibit more symptoms of depression, anxiety, loneliness, grief, and posttraumatic stress disorder than did their nonbereaved counterparts (Harper et al, 2014;Kreicbergs, Valdimarsdo´ttir, Onelo¨v, Henter, & Steineck, 2004;Nyberg et al, 2016). The situation could be even worse in Chinese culture if the child that has died is an only child.…”
mentioning
confidence: 99%
“…It is estimated from national census data (collected every 10 years) that the number of PLOCs in China is approximately 821,000, and this number is projected to reach 1.423 million in 2030 (Zhou & Mi, 2013). Although research has revealed strong evidence that losing a child is a tremendous threat to the mental health of parents (Harper, O’Connor, & O’Carroll, 2014; Nyberg, Hed Myrberg, Omerov, Steineck, & Nyberg, 2016), limited empirical studies have investigated the mental health of PLOCs in China, or possible protective factors.…”
mentioning
confidence: 99%
“…Losing a child is considered an enormous risk to the mental health status of parents (Harper, O'Connor, & O'Carroll, 2014; Hogan & Schmidt, 2002; Nyberg, Myrberg, Omerov, Steineck, & Nyberg, 2016; Rubin & Malkinson, 2001), even the loss of a child is perceived as the most difficult of all psychological traumas to overcome (Talbot, 2002). Specifically, bereaved parents are deep in grief over their lost child, experiencing more mental distress, such as anger, guilt, self‐blame, anxiety, depression and sadness than non‐bereaved parents (Cacciatore, Lacasse, Lietz, & Mcpherson, 2014; Harper et al., 2014; Marwit & Klass, 1994; Nyberg et al, 2016; Rogers, Floyd, Seltzer, Greenberg, & Hong, 2008; Talbot, 2002). In addition, bereaved parents are more likely to exhibit symptoms of posttraumatic stress disorder and complicated grief (Kreicbergs, Valdimarsdóttir, Onelöv, Henter, & Steineck, 2004; Nyberg et al., 2016), and it is difficult for them to struggle with (Kersting, Brähler, Glaesmer, & Wagner, 2011; Li, Stroebe, Chan, & Chow, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, bereaved parents are deep in grief over their lost child, experiencing more mental distress, such as anger, guilt, self‐blame, anxiety, depression and sadness than non‐bereaved parents (Cacciatore, Lacasse, Lietz, & Mcpherson, 2014; Harper et al., 2014; Marwit & Klass, 1994; Nyberg et al, 2016; Rogers, Floyd, Seltzer, Greenberg, & Hong, 2008; Talbot, 2002). In addition, bereaved parents are more likely to exhibit symptoms of posttraumatic stress disorder and complicated grief (Kreicbergs, Valdimarsdóttir, Onelöv, Henter, & Steineck, 2004; Nyberg et al., 2016), and it is difficult for them to struggle with (Kersting, Brähler, Glaesmer, & Wagner, 2011; Li, Stroebe, Chan, & Chow, 2014). The adverse suffering is magnified for bereaved parents when their dead child is the only one (Rogers et al., 2008; Wijngaards‐de Meij et al., 2005), as they are embedded in grief of the loss of their active parenthood and emotional attachment, and have to completely re‐define their identity and goals for the future (Floyd, Mailick Seltzer, Greenberg, & Song, 2013).…”
Section: Introductionmentioning
confidence: 99%